Dossier : Soigner par les lettres La bibliothérapie des Anciens (Mètis, 2017)
It is well known that texts and the meditation on texts are a therapy for the soul. In Antiquity, Greek and Roman doctors even considered reading, declaming or creating poetry as remedies for healing the body. This dossier of Mètis explores the paradoxical aspect of these ancient conceptions that link the body's health to literary activities and presuppose a physiology of reading and writing. It questions that form of « bibliotherapy » cultivated by the elite in the Greek and Roman world through the examples of epistolography (Cicero), rhetoric (Aelius Theon, Aelius Aristides) and medicine (Aristotle, Antyllus, Oribasius). The dossier maps these practices and conceptions of Antiquity in order to enrich contemporary reflexions on bibliotherapy, on the lost potentialities of the literary, or on holistic medicine.